Green Design dalam Desain Interior dan Arsitektur - Rachmayanti, Sri; Roesli, Christianto (Humaniora, 2014)
The purpose of this paper is to investigate the aspects that influence the interior and architecture that meet green design standards. Activities that supports environmentally friendly actions (Green Design will be assessed both in terms of function, space and material selection program or other efforts. The other thing is to analyze whether there are other efforts such as the using of sustainable materials or the using some types of plants to help revitalize the fresh air in the room. This journal is made based on the literature data and the results of interviews with Green Building Association. Green Design in the Planning office interiors is an effort that should be done together. If this effort is done collectively, the expected negative impact of global warming can be reduced.